2022
DOI: 10.1002/pro.4370
|View full text |Cite
|
Sign up to set email alerts
|

The free energy folding penalty accompanying binding of intrinsically disordered α‐helical motifs

Abstract: Intrinsically disordered proteins (IDPs) are abundant in eukaryotic proteomes and preform critical roles in many cellular processes, most often through the association with globular proteins. Despite lacking a stable three‐dimensional structure by themselves, they may acquire a defined conformation upon binding globular targets. The most common type of secondary structure acquired by these binding motifs entails formation of an α‐helix. It has been hypothesized that such disorder‐to‐order transitions are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The relatively low binding affinity determined for DREB2A(244-272)-R266G was due to decreased binding enthalpy, only partly compensated by entropy. This is in accordance with an analysis by Lah et al 49 , according to which DREB2A(244-272)-R266G would be energetically punished for having less residual structure, but also a higher degree of dynamics in the bound state oppositely reducing the folding penalty. The relation between residual helicity and the amount of formed structure in complex is understudied 21 .…”
Section: Discussionsupporting
confidence: 91%
“…The relatively low binding affinity determined for DREB2A(244-272)-R266G was due to decreased binding enthalpy, only partly compensated by entropy. This is in accordance with an analysis by Lah et al 49 , according to which DREB2A(244-272)-R266G would be energetically punished for having less residual structure, but also a higher degree of dynamics in the bound state oppositely reducing the folding penalty. The relation between residual helicity and the amount of formed structure in complex is understudied 21 .…”
Section: Discussionsupporting
confidence: 91%
“…We have previously analyzed the thermodynamics of the HigA2–HigB2 folding-upon-binding interaction and observed that the binding interface is highly optimized in terms of enthalpy, reaching similar levels as in the tightest protein complexes like barnase-barstar 27 . Given that the HigA2–HigB2 binding affinity is in the picomolar range, such strong optimization of interactions is necessary to compensate for the IDR folding free energy penalty, which for folding-upon-binding interactions can be as high as +3.5 kcal/mol 42 . Even though the penalty arising from the restriction of the IDR conformational space, in principle, lowers binding affinity, it is conceivable that it also stimulates the formation of stronger interactions, leading to increased specificity.…”
Section: Discussionmentioning
confidence: 99%
“…strongly exothermic) accompanied by a large entropic penalty, probably arising from mobility restriction, or even partial refolding, of some disordered regions upon binding, as observed in the circular dichroism spectra of the complexes, which overwhelms the favorable entropic contribution from dehydration of the binding interfaces. Strong enthalpic contributions are common in protein-protein interactions involving IDPs ( 63 , 64 ). In the cases where a considerable reduction of binding affinity was observed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Flexible, highly dynamic regions facilitate structural rearrangements necessary for allosteric interdomain regulation and for exposing different motifs to interact with different biological partners. Interactions in IDPs are often characterized by a moderate-to-low binding affinity and a transient nature, due to the energetic penalty stemming from the conformational change coupled to the binding ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%